Effectiveness of commercially available denture adhesives on retention of mandibular complete denture in resorbed mandibular ridge: An in vitro study - Indumathi Sivakumar; Tanx Qing Wen; Sara Luay Thanoon; Shivanii Prabakaren; Timothy Teo Yii; Thanesh Sinnathamby (Universidad de Concepción., 2024)
Background: Denture adhesives are alternatives used to improve retention, stability, comfort and satisfaction in patients with complete dentures. Evidence on the effectiveness of denture adhesives on resorbed mandibular ridges is scarce. Among the many commercially available denture adhesives, the ideal material for the severely resorbed mandibular ridge remains in dispute. Objective: The aim of this study was to evaluate the effectiveness of different quantities of four commercially available denture adhesives on the retention of mandibular complete dentures in severely resorbed ridges. Materials and Methods: A resorbed edentulous mandibular ridge model was manufactured in acrylic resin. A denture base was made and three loops were attached to it. Four commercially available denture adhesives (Fixodent, Perlie White, Fiftydent and Polident) were tested in amounts of 0.2 g, 0.4 g, 0.6 g, 0.8 g and 1.0 g. The acrylic resin model was evenly moistened with 1 ml of water and a weighted amount of adhesive material was applied to the denture base. The universal testing machine engaged the loops fixed on the denture base and applied the vertical displacement force. The maximum vertical displacement force values were recorded for each denture adhesive material at different amounts. Statistical calculation was performed using Kruskal Wallis with Bonferroni post hoc correction. Results: Statistically significant differences were observed in the mean values of the vertical displacement force for adhesive amounts of 0.2 g, 0.4 g, 0.6 g and 1.0 g (p<0.05) between the four adhesive materials tested. Statistically significant differences were observed when four denture adhesives were compared to each other in different amounts (p<0.05). Statistically significant differences were observed between different amounts for each of four denture adhesives (p<0.05). Conclusions: Among the four materials tested, Polident showed greater effectiveness at 0.6 g and 0.8 g, Fittydent at 0.6 g, 0.8 g and 1 g, Fixodent at 0.4 g and 0.6 g and Perlie White at 1 g and 0.8g quantity to resist vertical displacement. forces on the severely resorbed mandibular crest. Using an appropriate amount of denture adhesive allows for proper retention of the denture; Replacement of this adhesive is necessary once a day.